Cenobamate significantly improves seizure control in intellectually disabled patients with drug-resistant epilepsy and allows drug load reduction - Friedo, Anna-Lena; Greshake, Benedikt; Makridis, Konstantin L.; Straub, Hans-Beatus (Frontiers in Neurology, 2023)
Introduction Epilepsy patients with intellectual disability often suffer from drug-resistant epilepsy (DRE), which severely affects patients’ quality of life. Cenobamate (CNB) is a recently approved novel and effective ASM that can achieve high rates of seizure freedom in previously drug-resistant patients. Methods We performed a retrospective data analysis of the first patients treated with CNB at a single center. Outcome and treatment response were assessed at two different time points, and ASM burden was calculated. Results A 12 patients (7 males and 5 females) began treatment at a median age of 43 years, six of whom had developmental and epileptic encephalopathies. Prior to treatment with CNB, patients had tried a median of 13 different ASM. At the start of CNB therapy, patients were taking a median of 3 ASM. Treatment outcomes were available for 11 patients. After the first follow-up period (median 9 months), 55% of patients showed a significant seizure reduction of more than 50%, with three patients showing a reduction of more than 75% (27%). One patient achieved complete seizure freedom, while one patient did not respond to treatment. These response rates were consistently maintained at second follow-up after a median of 22 months. Ten patients (83%) reported adverse events (AE), the most common of which were dizziness and fatigue. No cases of drug reactions with eosinophilia and systemic symptoms (DRESS) were observed. The majority of AEs were mild and resolved over time. In addition, most patients were able to reduce their concomitant ASM. Discussion Cenobamate has been shown to be an effective ASM in patients with DRE and in patients with intellectual disabilities. After more than 1 year of treatment with CNB, close monitoring and management of drug–drug interactions may reduce enzyme-inducing ASMs and lead to better long-term outcomes. With CNB treatment, many patients can achieve a reduced overall drug burden while maintaining a reduction in seizures.